Cyp17a1 and cyp19a1 in the zebrafish testis are differentially affected by oestradiol - Hinfray, Nathalie; Nóbrega, Rafael Henrique [UNESP]; Caulier, Morgane; Baudiffier, Damien; Maillot-Maréchal, Emmanuelle; Chadili, Edith [UNESP]; Palluel, Olivier; Porcher, Jean-Marc; Schulz, Rüdiger; Brion, François (Bioscientifica, 2013)
Oestrogens can affect expression of genes encoding steroidogenic enzymes in fish gonads. However, little information is available on their effects at the protein level. In this context, we first analysed the expression of key steroidogenic enzyme genes and proteins in zebrafish testis, paying attention also to other cell types than Leydig cells. Gene expression was analysed by quantitative PCR on fluorescence-activated cell-sorting fractions coupled or not to differential plating, while protein synthesis was studied by immunohistochemistry using specific antibodies against zebrafish Cyp17a1, Cyp19a1a and Cyp19a1b. Furthermore, we have evaluated the effect of oestrogen treatment (17β-oestradiol (E2), 10 nM) on the localization of these enzymes after 7 and 14 days of in vivo exposure in order to study how oestrogen-mediated modulation of their expression is linked to oestrogen effects on spermatogenesis. The major outcomes of this study are that Leydig cells express Cyp17a1 and Cyp19a1a, while testicular germ cells express Cyp17a1 and both, Cyp19a1a and Cyp19a1b. As regards Cyp17a1, both protein and mRNA seem to be quantitatively dominating in Leydig cells. Moreover, E2 exposure specifically affects only Leydig cell Cyp17a1 synthesis, preceding the disruption of spermatogenesis. The oestrogen-induced suppression of the androgen production capacity in Leydig cells is a major event in altering spermatogenesis, while germ cell steroidogenesis may have to be fuelled by precursors from Leydig cells. Further studies are needed to elucidate the functionality of steroidogenic enzymes in germ cells and their potential role in testicular physiology. © 2013 Society for Endocrinology.
Keywords: Enzymes; Facs; Immunolocalization; Oestradiol; Steroidogenic; Testis; Zebrafish; aromatase; cyp17a1 protein; cytochrome P450 17; estradiol; unclassified drug; animal cell; animal tissue; controlled study; drug effect; estrogen therapy; gene expression; germ cell; immunohistochemistry; Leydig cell; nonhuman; polymerase chain reaction; priority journal; protein synthesis; synthesis; testis; zebra fish; Animals; Aromatase; Estradiol; Estrogens; Gene Expression; Germ Cells; Leydig Cells; Male; Spermatogenesis; Steroid 17-alpha-Hydroxylase; Zebrafish Proteins